Enhancing Community Health Literacy Through Education And Screening For Hypertension And Diabetes Mellitus Prevention In Batu Besar, Batam - Ika Novita Sari; Oktaviani, Fifin (Bhakti Sabha Nusantara, 2025)
Introduction: Non-communicable diseases (NCDs), particularly hypertension and diabetes mellitus, remain prevalent in Batu Besar Village, Batam City, and are influenced by limited health literacy and restricted access to healthcare services. This community service program aimed to improve community health literacy through health education and on-site health screening. Methods: A community-based intervention was conducted involving 30 adults and older adults aged 45–70 years with a history of or risk factors for hypertension and diabetes mellitus. Activities included health education, demonstrations of blood pressure and blood glucose self-monitoring, health screening, and individual counseling. Knowledge improvement was assessed using pre-test and post-test questionnaires. Results: Health screening showed that 60.0% of participants had stage 1 or stage 2 hypertension, 40.0% had prediabetes or diabetes mellitus, and 63.4% were overweight or obese. Post-test results indicated a significant increase in knowledge across all domains (p < 0.001), particularly in self-monitoring and dietary management. Conclusion Integrated education and community-based health screening effectively enhanced health literacy and supported early detection of NCDs in the community.